The first strawberries : a Cherokee story - Bruchac, Joseph, 1942-; Vojtech, Anna (New York : Puffin Books, 1998)
A quarrel between the first man and the first woman is reconciled when the Sun causes strawberries to grow out of the earth.
Elem. School Library Collection
School Library Journal
Wilson's Children
3.5
K-3
K-3
Keywords: Cherokee Indians -- Folklore; Cherokee Indians -- Folklore; Indians of North America -- Folklore; Strawberries -- Folklore; Cherokee Indians -- Folklore; Native Americans -- Folklore -- United States; Strawberries -- Folklore